TIGA-CUB-manualised psychoanalytic child psychotherapy versus treatment as usual for children aged 5–11 with treatment-resistant conduct disorders and their primary carers: results from a randomised controlled feasibility trial. Issue 3 (2nd September 2018) - Edginton, Elizabeth; Walwyn, Rebecca; Twiddy, Maureen; Wright-Hughes, Alex; Tubeuf, Sandy; Reed, Sadie; Smith, Alix; Stubbs, Laura; Birtwistle, Jacqueline; Abraham, Sarah Jane; Ellis, Lynda; Midgley, Nick; et al.
Abstract : Background: Parenting programmes are recommended for conduct disorders in 5–11 year olds, but ineffective for 25–33%. A feasibility trial was needed to determine whether a confirmatory trial of second-line, manualised short-term psychoanalytic child psychotherapy (mPCP) versus treatment as usual (TaU) is practicable. Method: This was a two-arm, pragmatic, parallel-group, multi-centre, individually-randomised controlled feasibility trial with blinded outcome assessment. Child–primary carer dyads were recruited from National Health Service Child and Adolescent Mental Health Services and mPCP delivered by routine child psychotherapists. Results: Thirty-two dyads (50% of eligible, 95% CI 37 to 63%) were recruited, with 16 randomised to each arm. Eleven (69%) completed ≥50% of 12 week mPCP and 13 (81%) ≥1 session. Follow-up was obtained for 24 (75%) at 4 months and 14/16 (88%) at 8 months. Teacher follow-up was 16 (50%). Manual adherence was good. Baseline candidate primary outcomes were 37.4 (SD 11.4) and 18.1 (SD 15.7) on the Child Behaviour Checklist/Teacher Report Form externalising scale and 102.8 (SD 28.4) and 58.8 (SD 38.9) on the total score. Health economics data collection was feasible and the trial acceptable to participants. Conclusion: Recruitment, teacher follow-up and the manual need some refinement. A confirmatory trial is feasible, subject to funding of research child psychotherapists.